Flame retardants for plastics and textiles : practical applications - Weil, Edward D. (Hanser Publications, 2009)
"For several years, the authors have taught a short course on flame retardancy under the auspices of the Business Communications Corp. This course has been found useful by persons entering the field of flame retardancy or who were facing particular problems of flame retarding plastics"--Provided by publisher.